2007
DOI: 10.1002/hed.20722
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of floor of mouth defects by the facial artery musculo‐mucosal flap following cancer ablation

Abstract: The FAMM flap is well suited for FOM reconstruction because it is reliable, has few significant complications, and allows preservation of oral function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 23 publications
(13 reference statements)
1
50
0
1
Order By: Relevance
“…These flaps can be used in reconstructive procedures other than oral cavity such as nasal cavity, orbit, and esophagus and skull base reconstructions. [23293839]…”
Section: Discussionmentioning
confidence: 99%
“…These flaps can be used in reconstructive procedures other than oral cavity such as nasal cavity, orbit, and esophagus and skull base reconstructions. [23293839]…”
Section: Discussionmentioning
confidence: 99%
“…Flaps as long as 8 cm can be transposed. Ayad's et al [45] series of 57 cases showed how tongue tethering can be avoided after repair of contiguous tongue/floor of mouth defects by closing the FOM defect with the flap and allowing the superior tongue defect to heal secondarily. This is a unique flap for quick, easy, low morbidity repair of mucosal defects of the mouth, lip and nose.…”
Section: Facial Artery Musculomucosal Flapmentioning
confidence: 97%
“…Disadvantages include limitations in size, including reach, and a somewhat higher rate of partial necrosis than seen in other axial patterned flaps. 27 Previous neck dissection and irradiation are proposed to be risk factors for necrosis.…”
Section: Facial Artery Myomucosal Flapmentioning
confidence: 99%
“…27 Anterior mandible defect with fibula segments in place anteriorly. Note skin paddle superiorly, which will be rotated internally for oral lining.…”
mentioning
confidence: 99%